The Analysis of Infant Death Determinants in Aceh Besar Regency of 2019 - Nilawati, Nilawati; Nurjannah, Nurjannah; Usman, Said; Saputra, Irwan; Bakhtiar, Bakhtiar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study deals with the analysis of infant death determinants in Aceh Besar Regency of 2019. One effort to get people to care and know a lot about their health and that of their families well needs a health literacy program. Pregnant women who have low health literacy reduce the success of early pregnancy detection efforts and increase the risk of death in infants or complications. This study is conducted by quantitative design using analytical methods with a Case Control approach. The result shows that there are relationship inter variables. And the most dominant variable in causing infant mortality in Aceh Besar Regeny of 2019 is socioeconomic.